A Scoping Review on Delaying Cognitive Decline and Dementia with Aging - Shan, Jiatong (Transactions on Materials, Biotechnology and Life Sciences, 2024)
There are a lot of elderly people who are suffering from decline in cognition or even the dementia like Alzheimer’s disease as they are aging. Although cognitive decline is an irreversible trend for all the human beings, related practitioners can do some interventions to delay this trend. This review summarizes the current interventions to delay the cognitive decline among the elderly people and prevent cognitive diseases like Alzheimer’s among them. The methods mainly include having healthier diets and performing healthier lifestyles. Most studies are performed in a longitudinal study which include several follow-ups which increase the preciseness and accuracy of the results. Results from current studies show that intaking healthier diets like drinking coffee and tea, eating mushroom as well as Mediterranean-DASH Intervention for Neurodegenerative Delay (MIND) diets, and doing healthier lifestyle are proved to have influence in delaying decline of cognition and other dementias like Alzheimer’s disease. This sheds light on future treatment on the cognitive diseases like Alzheimer’s disease among the elderly and have potentials to delay the cognitive decline.